Formulation and Evaluation of Body Scrub Using Flour-Based from Fruits of Indramayu Variety of Cengkir Mango (Mangifera indica L) - Ismanurrahman Hadi; Dadan Hidayattullah; Ade Irawan (Journal of Fundamental and Applied Pharmaceutical Science, 2022)
Cengkir Mango (Mangifera indica L) is a variety of mango known in the northern part of West Java and widely used as food, beverage, and natural-based pharmaceutical product. This fruit is potentially used as body scrub ingredients due to its richness in polyphenols contain. This study aims to formulate natural-based body scrub using the Cengkir Mango as an active ingredient. The formulation was divided into 3 groups with different concentrations of mango fruit flour, respectively 35, 46, and 50 grams (F1, F2, and F3). The product evaluation included homogeneity, stability, pH, and hedonic test. The organoleptic of body scrub indicated mango scent and light brownish-darker colors, responding to an increase of concentration for each formulation. The homogeneity test showed that the body scrub had no granulation of mango flour. The evaluation of pH showed the product had pH respectively at 7.5, 7.5, and 7.0 (F1, F2, and F3). These results indicated that the body scrub had good physical properties. Investigation of body scrub stability was used to evaluate the fragrance, color, and consistency of the formulation in storage for 3 weeks at room temperature. The results showed no change in color and consistency but a loss of mango fragrance after 3 weeks. The hedonic test indicated that most participants favored F1 (35 grams of mango flour). Based on these results, the flour of Cengkir mango had good performance as an active ingredient in a natural-based body scrub.